Changes in pore‐water chemistry and methane emission following the invasion of Spartina alterniflora into an oliogohaline marsh. (28th July 2017) - Tong, Chuan; Morris, James T.; Huang, Jiafang; Xu, Hui; Wan, Siang
Abstract: We measured methane emissions together with acetate, DMS, sulfate, and dissolved methane concentrations in pore waters from adjacent marsh plant communities in an oligohaline marsh of the Min River estuary, southeastern China—one community dominated by a native species, Cyperus malaccensis, the other by the exotic Spartina alterniflora . The objective was to determine if the exotic species altered soil pore‐water chemistry, metabolite pools, and methane emissions. We found that the invasive S. alterniflora, significantly increased the concentration of pore‐water acetate (6.1 vs. 1.2 μ M), but did not increase the pools of pore‐water DMS (54.6 vs. 45.9 nM). We observed significantly greater annual emissions of methane from the marsh areas dominated by S. alterniflora (15.1 vs. 5.1 mg m −2 h −1 annual average) and a significant correlation between annual methane emission rate and pore‐water acetate concentration at soil depths between 1 cm and 20 cm. There was no significant correlation between methane emission and the concentration of pore‐water DMS in either marsh community. The results indicate that a change in the dominant plant community can alter soil biogeochemistry. In particular, in an oligohaline environment, S. alterniflora supported higher rates of methane production than the native plant community. It probably does so through a variety of metabolic pathways, probably including acetoclastic methanongenesis.